2013
DOI: 10.1099/mic.0.064220-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy study of heterocyst differentiation in Anabaena PCC 7120 filaments

Abstract: Filamentous Anabaena PCC 7120 differentiates nitrogen-fixing specialized cells called heterocysts at regular intervals following removal of combined nitrogen from the medium. Phycobiliproteins are degraded during differentiation. Heterocyst differentiation was followed at the single cell level by using confocal fluorescence microscopy. The presence of an enhanced fluorescence emission peak from allophycocyanin (APC) indicates that the degradation of the phycobilisomes during nitrogen deprivation possibly initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As the heterocysts become mature, phycobilisome-induced red fluorescence completely disappears, so the degree of maturation of a specific (pro)heterocyst can be correlated to both the disappearance of red fluorescence and a change in size, shape, and envelopes with respect to adjacent vegetative cells (9, 11). The initial stages of differentiation, however, involve a transitory increase in red fluorescence that is interpreted to reflect disintegration of the phycobilisome structure as a result of a decrease in photosystem II in the differentiating cell (9).…”
Section: Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the heterocysts become mature, phycobilisome-induced red fluorescence completely disappears, so the degree of maturation of a specific (pro)heterocyst can be correlated to both the disappearance of red fluorescence and a change in size, shape, and envelopes with respect to adjacent vegetative cells (9, 11). The initial stages of differentiation, however, involve a transitory increase in red fluorescence that is interpreted to reflect disintegration of the phycobilisome structure as a result of a decrease in photosystem II in the differentiating cell (9).…”
Section: Observationmentioning
confidence: 99%
“…The initial stages of differentiation, however, involve a transitory increase in red fluorescence that is interpreted to reflect disintegration of the phycobilisome structure as a result of a decrease in photosystem II in the differentiating cell (9). Such an increase in fluorescence, actually involving a shift to shorter wavelengths (11), has been suggested as the first detectable sign of differentiation and therefore an early marker of cell differentiation.…”
Section: Observationmentioning
confidence: 99%
“…In this context, Piven et al (45) reported that nitrogen starvation and long term exposure to higher light intensities resulted in an increase in dephosphorylated linker proteins and partial disassembly of the PBS. Even studies in Nostoc 7120, which exhibit a bottom-to-top disassembly of the PBS in early heterocysts, suggest that dephosphorylation of linker proteins may act as a signal for degradation (46). Accordingly, one possible scenario could be that, when the V-shaped NblA-dimers penetrate the gap formed by four backto-back-assembled PBS ␤-subunits (27), the PBS structure disassembles (27), enabling dephosphorylation of the linker proteins by a phosphatase and opening the door for subsequent degradation.…”
Section: Heterologous Expression Of the Putative Protease Clpc 6803 -mentioning
confidence: 99%